ANALISIS PERBANDINGAN RENCANA ANGGARAN BIAYA DENGAN RENCANA ANGGARAN PELAKSANAAN (STUDI KASUS: PEMBANGUNAN RUMAH SUBSIDI PRITA RESIDENCE 2) - Septriansyah, Verinazul; Ismail, Muhammad; Umari, Zuul Fitriana; Asmawi, Bazar; Lubis, Lega Reskita (Program Studi Teknik Sipil, Fakultas Teknik, Universitas Tridinanti, 2025)
The development of the construction industry in Indonesia is progressing rapidly, as evidenced by the increasing number of buildings, bridges, roads, and other structures built to meet the needs of the community. In 2022, the population of Banyuasin reached 839,401 people, with 89.23% owning their own homes, 1.81% renting, 7.00% living rent-free, and the remaining 1.96% falling into other categories. The Permen PUPR 2023 method is a cost calculation approach that includes components such as labor, materials, and equipment to determine unit prices for specific types of work. Meanwhile, the real method involves calculating coefficients based on manual calculations of the quantities of materials and wages used, adjusted to the specific work being carried out. The aim of this research is to determine the total cost values calculated using both methods—Permen PUPR 2023 and the real method—and to compare the differences between these total costs in the construction of the Prita Residence 2 subsidized housing project. Cost estimation was conducted based on the building volume calculated from the project drawings. Based on data processing, the Permen PUPR 2023 method resulted in a cost of Rp. 137,874,758, while the real method yielded a cost of Rp. 97,316,225, with a percentage difference of 29.41%.